The steady-state behavior of the synthetic and side-sensitive synthetic double sampling (X)over-bar charts - Branco Costa, Antonio Fernando [UNESP]; Guerreiro Machado, Marcela Aparecida [UNESP] (Wiley-Blackwell, 2015)
The steady-state average run length is used to measure the performance of the recently proposed synthetic double sampling (X) over bar chart (synthetic DS chart). The overall performance of the DS X chart in signaling process mean shifts of different magnitudes does not improve when it is integrated with the conforming run length chart, except when the integrated charts are designed to offer very high protection against false alarms, and the use of large samples is prohibitive. The synthetic chart signals when a second point falls beyond the control limits, no matter whether one of them falls above the centerline and the other falls below it; with the side-sensitive feature, the synthetic chart does not signal when they fall on opposite sides of the centerline. We also investigated the steady-state average run length of the side-sensitive synthetic DS X chart. With the side-sensitive feature, the overall performance of the synthetic DS X chart improves, but not enough to outperform the non-synthetic DS X chart. Copyright (C) 2014 John Wiley &Sons, Ltd.
Keywords: (X)over-bar chart; Steady-state; Synthetic; Side-sensitive; Double sampling